Discrepancies in dyadic coping: associations with distress and quality of life in couples facing early stage dementia - Muijres, Peter; Weitkamp, Katharina; Bodenmann, Guy; Jenewein, Josef (Frontiers in Psychology, 2023)
Due to an ageing population, the number of people living with dementia (PWD) is. Caregiving partners (CGP) of PWD are often adopting additional tasks. The concept of dyadic coping (DC) addresses how couples cope with stress together. For dyadic coping to be successful, efforts of both partners should be equal. The current study examines how discrepancies in PWD and CGP perspectives on DC relate to distress and quality of life in each partner within couples facing early stage dementia (ESD).